Clawback [compact disc, unabridged] : an Ali Reynolds novel - Jance, Judith A. (Jance, Judith A. Ali Reynolds mysteries., 2016)
When her father is implicated in the murder of a man whose Ponzi scheme bankrupted hundreds of people, Ali Reynolds and her husband struggle to clear her father's name while seeking justice for the victims.